Spectral and Thermal Studies of Some Nucleic Acid Complexes - Masoud, Mamdouh S.; Fathalla, Magda F.; A. Mohamed, Rabah Hanem; Hassan, Maisa S. (Asian Journal of Chemistry, 2019)
Barbituric acid, thiobarbituric acid and thiouracil complexes with sodium and potassium chlorides were prepared and characterized by UV in different solvents and IR experimentally and theoretically using B3LYP method and Gaussian program. The composition of the studied complexes was also confirmed by elemental and thermal analysis, TG, DTA and DSC techniques to determine thermodynamic parameters (Ea, ΔH, ΔS and ΔG). The negative value of entropy of activation indicated the fragments have ordered structures than undecomposed complexes. The positive values of enthalpy of activation of the decomposition stages indicated that the process is endothermic. The positive values of free energy of the decomposition indicated non-spontaneous process. Evaluation of kinetics parameters were done. The isokinetic temperature β is 407 K, which is lower than experimental temperature range, confirming the processes is entropy control. However, the plots of ΔH versus ΔS for the complexes under investigation gave straight line indicating a close similarity in the mechanism.